Proceedings of the 3rd Workshop on Evaluating Vector Space Representations For 2019
DOI: 10.18653/v1/w19-2012
|View full text |Cite
|
Sign up to set email alerts
|

Dyr Bul Shchyl. Proxying Sound Symbolism With Word Embeddings

Abstract: This paper explores modern word embeddings in the context of sound symbolism. Using basic properties of the representations space one can construct semantic axes. A method is proposed to measure if the presence of individual sounds in a given word shifts its semantics of that word along a specific axis. It is shown that, in accordance with several experimental and statistical results, word embeddings capture symbolism for certain sounds. * https://en.wikipedia.org/wiki/Dyr bul shchyl 1 We also want to explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In their recent paper, [48] have challenged the broadly accepted idea that sound and meaning are not interdependent: unrelated languages very often use (or avoid) the same sounds for specific referents. [49] backs this idea up, showing that modern word embeddings capture such dependencies to a certain respect. In line with these ideas, one of the critical features of the model that we discuss below is its concatenated embedding that contains information on the phonetics of every word preprocessed by a bi-directional LSTM alongside with its vectorized semantic representation.…”
Section: Importance Of Phoneticsmentioning
confidence: 96%
“…In their recent paper, [48] have challenged the broadly accepted idea that sound and meaning are not interdependent: unrelated languages very often use (or avoid) the same sounds for specific referents. [49] backs this idea up, showing that modern word embeddings capture such dependencies to a certain respect. In line with these ideas, one of the critical features of the model that we discuss below is its concatenated embedding that contains information on the phonetics of every word preprocessed by a bi-directional LSTM alongside with its vectorized semantic representation.…”
Section: Importance Of Phoneticsmentioning
confidence: 96%
“…In a massive study across nearly two-thirds of the world's languages (Blasi et al, 2016) managed to demonstrate that a considerable proportion of 100 essential vocabulary items carry strong associations with specific kinds of human speech sounds, occurring persistently across continents and linguistic lineages. (Yamshchikov et al, 2019) showed that modern methods of computational linguistics could be used to highlight such associative structures within a language.…”
Section: Introductionmentioning
confidence: 99%